Integrated Bioinformatics Analysis Identifies Robust Biomarkers and Its Correlation With Immune Microenvironment in Nonalcoholic Fatty Liver Disease - Zhang, Feng; Zhang, Zhengwei; Li, Yapeng; Sun, Yi; Zhou, Xinliang; Chen, Xiaoning; Sun, Shibo (Frontiers in Genetics, 2022)
Objective: Non-alcoholic fatty liver disease (NAFLD) is a serious threat to human health worldwide. In this study, the aim is to analyze diagnosis biomarkers in NAFLD and its relationship with the immune microenvironment based on bioinformatics analysis. Methods：We downloaded 2 microarray datasets (GSE48452, GSE63067) from the Gene Expression Omnibus (GEO) database for screening differentially expressed genes (DEGs). The hub genes were screened by a serious of machine learning analysis, such as SVM, LASSO, and WGCNA analysis. It is worth mentioning that we used gene enrichment analysis to explore the driver pathways of NAFLD occurrence. Subsequently, the above genes were validated by external datasets (GSE66676). Moreover, the CIBERSORT algorithm was used to estimate the proportion of different types of immune cells. Finally, the Spearman analysis was used to vertify the relationship between hub genes and immune cells. Result：Hub genes (CAMK1D, CENPV and TRHDE) were identified. In addion, we found that the pathogenesis of NAFLD is mainly related to nutritional metabolism and the immune system. In correlation analysis, CENPV expression had a strong negative correlation with T cells CD4 memory resting, and TRHDE expression had a strong positive correlation with B cells naive. Conclusion: CAMK1D, CENPV and TRHDE play regulatory roles in NAFLD. In particular, CENPV and TRHDE may regulate the immune microenvironment by mediating T cells CD4 memory resting and B cells naive, respectively, and thus influence disease progression.